Biological reconstruction of the Late Neolithic Lengyel Culture - Köhler, Kitti (Dissertationes Archaeologicae, 2013)
Abstract of PhD thesis submitted in 2013 to the Doctoral School of Biology, Eötvös Loránd University, Budapest under the supervision of Gyula Gyenis. Between 2006 and 2009 rescue excavations preceding the construction of M6 Motorway were carried out, in the course of which a settlement and a related cemetery of more than two thousand graves of the Late Neolithic-Early Copper Age Lengyel culture have been excavated at the site of Alsónyék-Bátaszék, in Southeastern Transdanubia (Tolna county). Present study considers the northern, so-called 010/B part of the site (cemetery), comprising 862 graves. According to the current archaeological consensus earlier Central European Linearbandkeramik culture (LBK) played a crucial role in the formation of the Lengyel culture, but an infiltration or migration of new populations during this time period cannot be excluded. Present dissertation has been designed to investigate this fundamental question. In addition, I completed a detailed demographic analysis and published the frequency data of several pathological and dental alterations. In the course of the still ongoing investigation a case showing the classic symptoms of tuberculosis had been found.